Wrecked [compact disc, unabridged] - Clark, Carol Higgins (Clark, Carol Higgins. Regan Reilly mystery (Simon & Schuster Audio (Firm)), 2010)
Private Investigator Regan Reilly and her husband Jack travel to Cape Cod to celebrate their first wedding anniversary and enjoy a romantic stay at Jack's parents' beachfront home. However, when the home's caretaker discovers the body of neighbor and notorious shut-in Adele Hopkins on the beach after a violent storm, Jack and Regan must put their romantic plans on hold to discover the deceased's next of kin.